Aluminum-plastic film and base material for aluminum-plastic film
Through the co-extrusion technology of aluminum-plastic film, combined with the polyester layer, composite resin layer and polyamide layer, the problem of environmental pollution and insufficient adhesion caused by the use of solvents in the packaging material is solved, and an efficient and environmentally friendly battery packaging material is achieved. It has good bonding and electrolyte resistance.
Patent Information
- Application Number
- CN202310742667.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-15
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-17
AI Technical Summary
The use of solvents in the production process of existing packaging materials leads to environmental pollution, and the connection between the multi-layer films is insufficient, making it difficult to meet the protection needs of different uses, especially in the battery manufacturing process, which requires heat resistance, insulation, flexibility and electrolysis resistance. Liquidity.
Aluminum-plastic film is used, including a polyester layer, a composite resin layer and a polyamide layer, and is formed integrally by coextrusion. The composite resin layer contains terpolymers, which contain ethylene-butyl acrylate structural units and terpolymers. The content of the substance is greater than 45 weight percent, and the polyester layer and the polyamide layer are combined to form a film with good bonding and transparency.
It realizes the solvent-free manufacturing process, improves the intersect strength and transparency between multi-layer films, is suitable for battery packaging, has electrolyte resistance and heat resistance, simplifies the manufacturing process and reduces costs.
Smart Images

Figure CN119141977A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an aluminum-plastic film and a substrate for the aluminum-plastic film, and in particular to an aluminum-plastic film applied to a battery and a substrate for the aluminum-plastic film. Background Art
[0002] As far as packaging materials are concerned, it is difficult to achieve ideal protection with a single material. Therefore, most packaging materials on the market are made of multiple layers of film, and the ideal protection effect can be achieved by combining or matching different films.
[0003] Common film lamination methods include coating and laminating. However, the adhesive layer laminating method requires the use of solvents, which are harmful to the environment. Therefore, the existing packaging materials still need to be improved in terms of manufacturing methods.
[0004] In addition to protection, the adhesion between multi-layer films is also a characteristic that packaging materials need to focus on. When the packaging application is different, the market's expected adhesion strength will also be different.
[0005] For example, when the packaging material is used to encapsulate a battery pack and an electrolyte, the packaging material needs to have a certain degree of heat resistance, insulation, flexibility, electrolyte resistance and stretchability so as to be suitable for various processing steps in the battery manufacturing process.
[0006] Therefore, how to improve the materials to make the packaging materials have ideal protective effects and enhance the adhesion between multi-layer films so that they can be applied to various uses and overcome the environmentally unfriendly defects of solvents has become one of the important issues that this business wants to solve. Summary of the invention
[0007] The technical problem to be solved by the present application is to provide an aluminum-plastic film and a substrate for the aluminum-plastic film in view of the deficiencies in the prior art.
[0008] In order to solve the above technical problems, one of the technical solutions adopted in the present application is to provide an aluminum-plastic film. The aluminum-plastic film includes a polyester layer, a composite resin layer, a polyamide layer and an aluminum metal layer. The composite resin layer is arranged between the polyester layer and the polyamide layer, and the aluminum metal layer is arranged on the polyamide layer. The polyester layer, the composite resin layer and the polyamide layer are integrally formed by co-extrusion. The composite resin layer includes a terpolymer and a polyolefin resin, and the total weight of the composite resin layer is 100 weight percent, the content of the terpolymer is greater than 45 weight percent, and the terpolymer contains ethylene-butyl acrylate structural units.
[0009] Furthermore, the terpolymer is a copolymer synthesized from ethylene monomer, butyl acrylate monomer and acrylic acid monomer.
[0010] Furthermore, based on the total weight of the terpolymer being 100%, the weight ratio of the ethylene monomer to the butyl acrylate monomer in the terpolymer is 14% to 20%.
[0011] Furthermore, the terpolymer is grafted with maleic anhydride.
[0012] Furthermore, maleic anhydride is grafted onto the ethylene monomer, and the grafting rate of maleic anhydride is 5wt% to 15wt%.
[0013] Furthermore, the weight ratio of the terpolymer to the polyolefin resin in the composite resin layer is 1:1 to 3:1.
[0014] Furthermore, the polyester layer is made of polyethylene terephthalate, the intrinsic viscosity of polyethylene terephthalate is 0.60 to 0.68, and the melting point of polyethylene terephthalate is 240° C. to 250° C.
[0015] Furthermore, the number average molecular weight of the material forming the polyamide layer is 20000 g / mol to 23000 g / mol, the relative viscosity of the material forming the polyamide layer is 2.7 to 2.9, and the melting point of the material forming the polyamide layer is 215° C. to 225° C.
[0016] In order to solve the above-mentioned technical problems, another technical solution adopted in the present application is to provide a substrate for aluminum-plastic film. The substrate for aluminum-plastic film includes a polyester layer, a composite resin layer and a polyamide layer. The composite resin layer is arranged between the polyester layer and the polyamide layer, and the polyester layer, the composite resin layer and the polyamide layer are integrally formed by coextrusion. The composite resin layer includes a terpolymer and a polyolefin resin, and the total weight of the composite resin layer is 100 weight percent, the content of the terpolymer is greater than 45 weight percent, and the terpolymer contains ethylene-butyl acrylate structural units.
[0017] Furthermore, the haze of the substrate used for the aluminum-plastic film is less than 5%.
[0018] One of the beneficial effects of the present application is that the aluminum-plastic film and the substrate for the aluminum-plastic film provided by the present application can achieve transparency and good bonding properties through the technical scheme of "the total weight of the composite resin layer is 100 weight percent, and the content of the terpolymer is greater than 45 weight percent", "the terpolymer contains ethylene-butyl acrylate structural units" and "the polyester layer, the composite resin layer and the polyamide layer are integrally formed by co-extrusion".
[0019] To further understand the features and technical contents of the present application, please refer to the following detailed description and drawings of the present application. However, the drawings provided are only for reference and illustration and are not intended to limit the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic side view of the aluminum-plastic film of the present application.
[0021] Figure 2 It is a schematic side view of a substrate for an aluminum-plastic film of the present application. DETAILED DESCRIPTION
[0022] The following is to illustrate the implementation methods of the "aluminum-plastic film and a substrate for aluminum-plastic film" disclosed in the present application through specific specific examples. Those skilled in the art can understand the advantages and effects of the present application from the content disclosed in this specification. The present application can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the concept of the present application. In addition, the drawings of the present application are only simple schematic illustrations, not depictions based on actual sizes, and are stated in advance. The following implementation methods will further explain the relevant technical content of the present application in detail, but the disclosed content is not intended to limit the scope of protection of the present application. In addition, the term "or" used herein may include any one or more combinations of the associated listed items depending on the actual situation.
[0023] See also Figure 1 As shown, Figure 1 1 is a schematic side view of the aluminum-plastic film of the present application. The aluminum-plastic film 1 includes a substrate 2 for the aluminum-plastic film and an aluminum metal layer 3. The aluminum metal layer 3 can be arranged on the substrate 2 for the aluminum-plastic film by gluing, but the present application is not limited to this arrangement, as long as the aluminum metal layer 3 can be fixed on the substrate 2 for the aluminum-plastic film.
[0024] In the present application, the substrate 2 for the aluminum-plastic film is formed in one piece by coextrusion. In the process of manufacturing the substrate 2 for the aluminum-plastic film, the step of coating and gluing is not excluded. Since no viscose is used, no solvent-based solution is required, and there is no problem of layer falling off due to aging of the viscose. Therefore, the substrate 2 for the aluminum-plastic film has the advantages of simple manufacturing process and environmental protection.
[0025] See also Figure 2 As shown, Figure 2 The side view of the substrate 2 used for the aluminum-plastic film of the present application is shown in FIG. The substrate 2 used for the aluminum-plastic film includes a polyester layer 21 , a composite resin layer 22 and a polyamide layer 23 .
[0026] When used in battery outer packaging materials, the polyester layer 21 will contact the electrolyte, so the polyester layer 21 needs to have good electrolyte resistance and heat resistance. The polyamide layer 23 will contact the aluminum metal layer 3. In order to protect other layers, the polyamide layer 23 needs to have good puncture resistance to ensure the safety of battery use. In an exemplary embodiment, the thickness of the substrate 2 used for the aluminum-plastic film is 15 microns to 45 microns, but the present application is not limited thereto.
[0027] Due to the difference in material properties, polyester and polyamide cannot be combined by hot melt. If polyester and polyamide are directly co-extruded, the material will be delaminated and cannot form a composite film. Therefore, the present application selects a specific composite resin material to form a composite resin layer 22 between the polyester layer 21 and the polyamide layer 23. The composite resin layer 22 can be combined with the polyester layer 21 and the polyamide layer 23 respectively, so that the aluminum-plastic film 1 has sufficient peel strength and appropriate tensile strength.
[0028] Furthermore, the composite resin layer 22 needs to have high transparency and low haze properties to maintain the high transparency and low haze properties of the substrate 2 used for the aluminum-plastic film. In this way, it is convenient to check whether the aluminum-plastic film 1 has defects after punching, and whether the barcode on the aluminum metal layer 3 is clear, which is beneficial to quality control.
[0029] In the present application, the material forming the composite resin layer 22 includes a terpolymer, which has polarity. The addition of the terpolymer can provide a good bonding effect between the polyester layer 21, the composite resin layer 22 and the polyamide layer 23.
[0030] The terpolymer contains repeating structural units of ethylene-butyl acrylate. That is, the monomers for synthesizing the terpolymer include ethylene and butyl acrylate.
[0031] In an exemplary embodiment, the terpolymer is a copolymer synthesized from ethylene monomer, butyl acrylate monomer and acrylic acid monomer, and these three monomers are copolymerized simultaneously to form the terpolymer. In this way, the terpolymer can have polarity and can have a good bonding effect with the polyester layer 21 and the polyamide layer 23 at the same time. However, the present application is not limited thereto.
[0032] In order to improve the bonding effect, the weight ratio of the ethylene monomer to the butyl acrylate monomer in the terpolymer can be controlled. In an exemplary embodiment, the total weight of the terpolymer is 100 weight percent, and the total amount of the ethylene monomer and the butyl acrylate monomer in the terpolymer is 14 weight percent to 20 weight percent. For example, the molar content of butyl acrylate in the monomers for synthesizing the terpolymer can be 15%, 16%, 17%, 18% or 19%.
[0033] In an exemplary embodiment, the Shore hardness of the terpolymer is 85A to 90A. The melt index of the terpolymer measured at 190°C / 2.16kg is 6.5 to 7.5.
[0034] To further enhance the bonding effect, the terpolymer is grafted with maleic anhydride segments. In an exemplary embodiment, ethylene monomer grafted with maleic anhydride segments is selected to synthesize the terpolymer. Specifically, the grafting rate of maleic anhydride on ethylene is 5wt% to 15wt%.
[0035] In the composite resin layer 22, the content of the terpolymer must reach a certain level to achieve a good bonding effect. Specifically, with the total weight of the composite resin layer 22 being 100 weight percent, the content of the terpolymer in the composite resin layer 22 is greater than or equal to 45 weight percent.
[0036] Preferably, the content of the terpolymer in the composite resin layer 22 is greater than or equal to 50 weight percent. For example, the content of the terpolymer in the composite resin layer 22 can be 55 weight percent, 60 weight percent, 65 weight percent, 70 weight percent, 75 weight percent, 80 weight percent, 85 weight percent, 90 weight percent, 95 weight percent or 100 weight percent.
[0037] In addition to the terpolymer, the material forming the composite resin layer 22 may further include a polyolefin resin. The addition of the polyolefin resin can achieve the effect of reducing costs and improve the extensibility of the composite resin layer 22, so as to facilitate the subsequent elongation manufacturing process. However, it should be noted that the content of the terpolymer in the composite resin layer 22 must still be maintained at greater than or equal to 45 weight percent.
[0038] In an exemplary embodiment, the polyolefin resin is low-density polyethylene. The polyolefin resin has good compatibility with the terpolymer so as to form the composite resin layer 22 together without negatively affecting the extensibility of the composite resin layer 22, and low-density polyethylene is preferred. In addition, the substrate 2 used for the aluminum-plastic film can have the characteristics of high transparency and low haze.
[0039] In some embodiments, the polyester layer 21 is made of polyethylene terephthalate with a melting point of 240° C. to 250° C., and the intrinsic viscosity of polyethylene terephthalate is 0.60 to 0.68. The polyamide layer 23 is made of nylon 6 (or polycaprolactam) with a molecular weight of 20,000 g / mol to 23,000 g / mol, the relative viscosity of nylon 6 is 2.7 to 2.9, the melting point of nylon 6 is 215° C. to 225° C., and the peroxide value of nylon 6 is 42±2 meq / kg.
[0040] When manufacturing a substrate 2 for aluminum-plastic film, it includes at least the following steps: drying raw materials (S1); using the raw materials to co-extrude a composite laminate in three layers (S2); biaxially stretching the composite laminate to a desired thickness (S3); heat-fixing the stretched composite laminate to obtain the substrate 2 for aluminum-plastic film (S4); and after cooling, rolling up the substrate 2 for aluminum-plastic film (S5).
[0041] To facilitate the description of the efficacy of the present application, the substrate 2 for aluminum-plastic film of Examples 1 and 2 and Comparative Example 1 were prepared according to the above steps S1 to S5, and the differences and characteristic results are listed in Table 1.
[0042] [Example 1]
[0043] In step S1, polyethylene terephthalate (hereinafter referred to as PET), a composite resin material (a material forming the composite resin layer 22) and nylon 6 are placed in an environment with a temperature of 110°C to 130°C and a dew point of -40°C and dried for 6 to 8 hours. The composite resin material includes a terpolymer and a low-density polyethylene (hereinafter referred to as LDPE) in a weight ratio of 1:1. The terpolymer (hereinafter referred to as EBA-AA) is a copolymer formed by the co-polymerization of ethylene monomer, butyl acrylate monomer and acrylic acid monomer. Among them, 5wt% to 15wt% of maleic anhydride is grafted onto the ethylene monomer. In this specification, the grafting rate is defined as (weight after grafting-weight before grafting) / (weight before grafting)×100%.
[0044] In step S2, in the three-layer co-extrusion device, the processing temperatures of the screws are 260° C., 250° C., and 250° C., respectively, to form the polyester layer 21, the composite resin layer 22, and the polyamide layer 23 in sequence. The temperature of the feed block is 250° C. The thicknesses of the polyester layer 21, the composite resin layer 22, and the polyamide layer 23 after the three-layer co-extrusion are 40 μm, 16 μm, and 144 μm, respectively. The total thickness of the composite laminate is 200 μm.
[0045] After the biaxial stretching in step S3, the thicknesses of the polyester layer 21, the composite resin layer 22 and the polyamide layer 23 are 5 microns, 2 microns and 18 microns respectively. The total thickness of the substrate 2 for the aluminum-plastic film is 25 microns.
[0046] The haze and transmittance measuring machine (model: X-ritecolor eye 7000A) produced by X-Rite, USA, was used to measure the haze and visible light transmittance of the substrate 2 used for the aluminum-plastic film according to the standard test method ASTM D1003 formulated by the American Society for Testing and Materials. It can be seen from the results that the haze of the substrate 2 used for the aluminum-plastic film is 3.7%, and the visible light transmittance of the substrate 2 used for the aluminum-plastic film is 91.6%.
[0047] The tensile strength of the substrate 2 for aluminum-plastic film was measured using a tensile strength measuring machine (model: Shimadzu AG-X) according to the standard test method ASTM D882 established by the American Society for Testing and Materials. The results show that the tensile strength of the substrate 2 for aluminum-plastic film is 9.7 kg / cm 2 .
[0048] In order to evaluate the interlayer bonding strength of the substrate 2 for aluminum-plastic film, the substrate 2 for aluminum-plastic film was torn by hand, and its cross section was found to be serrated. That is to say, in Example 1, the bonding strength between the layers was relatively poor.
[0049] [Example 2]
[0050] The raw materials and operation methods used in Example 2 are similar to those in Example 1, except that the weight ratio of the terpolymer (copolymer of ethylene, butyl acrylate and acrylic acid) to the low-density polyethylene in the composite resin material is 3:1.
[0051] In Example 2, the total thickness of the substrate 2 for the aluminum-plastic film is 25 microns. After measurement, the haze of the substrate 2 for the aluminum-plastic film is 1.2%, the visible light transmittance of the substrate 2 for the aluminum-plastic film is 91.3%, and the tensile strength of the substrate 2 for the aluminum-plastic film is 12.4 kg / cm 2 The substrate 2 for aluminum-plastic film was torn by hand and found to have a smooth cross section. That is, in Example 2, the bonding strength between the layers was good.
[0052] [Comparative Example 1]
[0053] The raw materials and operation methods used in Comparative Example 1 are similar to those of Example 2, except that polyethylene terephthalate is added to the composite resin material and mixed with the terpolymer. The weight ratio of the terpolymer (copolymer of ethylene, butyl acrylate and acrylic acid) to polyethylene terephthalate in the composite resin material is 3:1.
[0054] In Comparative Example 1, the total thickness of the substrate 2 for the aluminum-plastic film is 25 microns. After measurement, the haze of the substrate 2 for the aluminum-plastic film is 25.7%, the visible light transmittance of the substrate 2 for the aluminum-plastic film is 93.5%, and the tensile strength of the substrate 2 for the aluminum-plastic film is 13.6 kg / cm 2 The cross section of the aluminum-plastic film substrate 2 was found to be flat but slightly uneven by hand tearing. That is, in Comparative Example 1, the bonding strength between the layers was acceptable.
[0055] Table 1
[0056]
[0057] The experimental results show that when the content of the terpolymer in the composite resin layer 22 is greater than 45 weight percent, the composite resin layer 22 can be combined with the polyester layer 21 and the polyamide layer 23 by coextrusion, and has good bonding strength. Therefore, the present application can avoid the defects of the previous manufacturing of composite film layers requiring secondary processing or adhesive layer bonding, and has the advantage of being convenient for downstream manufacturers to use.
[0058] Furthermore, the provision of the composite resin layer 22 does not negatively affect the visible light transmittance of the substrate 2 for the aluminum-plastic film. Specifically, the visible light transmittance of the substrate 2 for the aluminum-plastic film is greater than 90%.
[0059] When polyolefin resin is added and mixed with the terpolymer, not only the cost can be reduced, but also the elongation of the composite resin layer 22 can be improved. From the results in Table 1, it can be seen that the tensile strength of the substrate 2 for aluminum-plastic film in Examples 1 and 2 is lower than the tensile strength of the substrate 2 for aluminum-plastic film in Comparative Example 1. Specifically, the tensile strength of the substrate 2 for aluminum-plastic film of the present application is 8 kg / cm 2 Up to 13kg / cm 2 .
[0060] Moreover, compared with adding polyethylene terephthalate, adding polyolefin resin can maintain the low haze property of the substrate 2 for aluminum-plastic film, so as to be suitable for various uses. Specifically, the haze of the substrate 2 for aluminum-plastic film is less than 5%, preferably less than 4%, and more preferably less than 3%.
[0061] [Beneficial Effects of Embodiments]
[0062] One of the beneficial effects of the present application is that the aluminum-plastic film and the substrate for the aluminum-plastic film provided by the present application can achieve transparency and good bonding properties through the technical scheme of "the total weight of the composite resin layer is 100 weight percent, and the content of the terpolymer is greater than 45 weight percent", "the terpolymer contains ethylene-butyl acrylate structural units" and "the polyester layer, the composite resin layer and the polyamide layer are integrally formed by co-extrusion".
[0063] Furthermore, the material selection of the present application is designed for battery packaging materials. The selected terpolymer itself has the characteristics of high transparency and low haze, and the terpolymer can have good adhesion with polyester and polyamide at the same time. Therefore, the substrate used for the aluminum-plastic film of the present application can be directly prepared by co-extrusion, which has the advantage of simple manufacturing.
[0064] In order to optimize the bonding effect, the present application selects a terpolymer containing at least ethylene and butyl acrylate repeating structural units, and adjusts the weight ratio of butyl acrylate in the monomers synthesizing the terpolymer. It is further found that when ethylene, butyl acrylate and acrylic acid are used as monomers for synthesizing the terpolymer, the terpolymer can have a good bonding effect with polyester and polyamide. In addition, a terpolymer grafted with maleic anhydride can also be selected.
[0065] On the other hand, the present application also regulates the composition characteristics of the polyester layer and the polyamide layer to optimize the bonding strength between the layers in a bidirectional manner and enhance the characteristics of the aluminum-plastic film (for example, electrolyte resistance, heat resistance, and puncture resistance).
[0066] The contents disclosed above are only preferred feasible embodiments of the present application, and are not intended to limit the protection scope of the claims of the present application. Therefore, all equivalent technical changes made using the contents of the present application specification and drawings are included in the protection scope of the claims of the present application.
Claims
1. An aluminum-plastic film, It is characterized in that The aluminum-plastic film comprises: a polyester layer; a composite resin layer, comprising a terpolymer and a polyolefin resin, wherein the total weight of the composite resin layer is 100 weight percent, the content of the terpolymer is greater than 45 weight percent, and the terpolymer comprises an ethylene-butyl acrylate structural unit; a polyamide layer, the composite resin layer is disposed between the polyester layer and the polyamide layer, and the polyester layer, the composite resin layer and the polyamide layer are integrally formed by co-extrusion; and An aluminum metal layer is disposed on the polyamide layer.
2. The aluminum-plastic film according to claim 1, It is characterized in that The terpolymer is a copolymer synthesized from ethylene monomer, butyl acrylate monomer and acrylic acid monomer.
3. The aluminum-plastic film according to claim 2, It is characterized in that Taking the total weight of the terpolymer as 100%, the weight ratio of the ethylene monomer to the butyl acrylate monomer in the terpolymer is 14% to 20%.
4. The aluminum-plastic film according to claim 1, It is characterized in that The terpolymer is grafted with maleic anhydride.
5. The aluminum-plastic film according to claim 2, It is characterized in that Maleic anhydride is grafted onto the ethylene monomer, and the grafting rate of the maleic anhydride onto the ethylene monomer is 5wt% to 15wt%.
6. The aluminum-plastic film according to claim 1, It is characterized in that The weight ratio of the terpolymer to the polyolefin resin in the composite resin layer is 1:1 to 3:
1.
7. The aluminum-plastic film according to claim 1, It is characterized in that The polyester layer is made of polyethylene terephthalate, the intrinsic viscosity of the polyethylene terephthalate is 0.60 to 0.68, and the melting point of the polyethylene terephthalate is 240° C. to 250° C.
8. The aluminum-plastic film according to claim 1, It is characterized in that The number average molecular weight of the material forming the polyamide layer is 20000 g / mol to 23000 g / mol, the relative viscosity of the material forming the polyamide layer is 2.7 to 2.9, and the melting point of the material forming the polyamide layer is 215° C. to 225° C.
9. A substrate for aluminum-plastic film, It is characterized in that The base material for the aluminum-plastic film comprises: a polyester layer; a composite resin layer, comprising a terpolymer and a polyolefin resin, wherein the total weight of the composite resin layer is 100 weight percent, the content of the terpolymer is greater than 45 weight percent, and the terpolymer comprises an ethylene-butyl acrylate structural unit; and A polyamide layer, the composite resin layer is arranged between the polyester layer and the polyamide layer, and the polyester layer, the composite resin layer and the polyamide layer are integrally formed by co-extrusion.
10. The substrate for aluminum-plastic film according to claim 9, It is characterized in that The haze of the substrate for the aluminum-plastic film is less than 5%.
Citation Information
Patent Citations
Heat shrinkable multilayer film and tube with improved adhesion after orientation
CN101351329A
Co-extrusion biaxial-orientation polyamide film containing polyester layer and preparation method thereof
CN106671534A
Composition comprising ethylene copolymers and polyolefin
CN1930231A
laminate
JP1992261846A
